Limited Renal Intravascular Lymphoma: A Case Report and Review of the Literature - Guillermo Enrique Quintero Vega; Daniel Osorio; José Antonio de la Hoz Valle; Daniela Rodríguez Feria (Case Reports in Oncological Medicine)
Intravascular large B-cell lymphoma (IVLBCL) is a rare subtype of non-Hodgkin lymphoma. It is characterized by the proliferation of cancerous cells into the intraluminal space of the blood vessels. It has a low incidence rate of 0.095 cases per 1,000,000. The clinical presentation is insidious and unspecific, often delaying the diagnosis. IVLBCL can be diagnosed through body images and histopathology analysis. This neoplasm averages a 60% response rate to current chemotherapy treatment, favoring rituximab, and doxorubicin-based regimen if it is diagnosed in time. Here, we present the case of a 56-year-old man admitted to our hospital with a fever who was eventually diagnosed with IVLBCL. He presented to the consultation with anemia, fever, and splenomegaly. An infection panel, a bone marrow biopsy, and a PET-CT scan were performed and ruled out the possibility of infections and neoplasms. The patient later developed edematous syndrome. As a result, a renal biopsy was performed which tested positive for intravascular large B-cell lymphoma. Currently, the patient has been in complete remission for 33 months. Along with presenting this specific case, we also reviewed previously published cases of IVLBCL to illustrate the renal involvement of this pathology.